Sustainability of Scientific Journals in the Developing World With Special Reference to Bangladesh - Hasan Shareef Ahmed; A. Mushtaque R. Chowdhury; M. Shamsul Islam Khan; A. K. M. Ahsan Ullah (Journal of Applied Communications, 1999)
The study explores sustainability of scientific journal publication in Bangladesh. Forty-three journal editors were interviewed, and 66 current journals were physically examined for production quality, regularity of publication, and availability at concerned libraries. Findings revealed that 68% of the journals were published late, 30% had inconsistencies in typesetting, and 14% were indexed. Most journals were found either excellent or of good quality in terms of printing (85%), binding (77%), paper (92%), and graphic reproduction (76%). Most journals were not available in major libraries under study. Of the 43 editors, 28 (35%) reported a cost recovery of 1-45% from subscriptions, advertisements, and sales. About 74.4% of the editors did not consider their journals at risk. Although 86% of the editors were confident that their journals would be sustained in the long run, 37.3% could not give any convincing logic in support of their statement. Major problems include lack of skilled staff, finance, quality articles and institutional support, and lengthy peer review process. Only one journal editor was found to be a full-time editor having training in editing and publication. One-half (51%) of the editors reported have training in editing, while four had publication training. Most editors (79%) were interested in acquiring training in editing and publication. Institutional support and backup, enthusiasm and zeal of editors, unmet need for standard local journals, constant flow of funds and articles, and skilled manpower are instrumental for sustainability of science journals in Bangladesh.